The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.2535/ofaj1936.69.2-3_85
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study of the Accessory Mental Foramen and the Distribution of Its Nerve

Abstract: We examined the range of the accessory mental foramen [AMF] and its accessory mental nerve in three Japanese cadavers. The diameters of the AMF were relatively small: 0.74 mm, 0.80 mm and 0.89 mm. The distances between the mental foramen and AMF were: 0.67 mm, 2.1 mm and 5.74 mm. The distribution of the accessory mental nerve was different in the three cases. These nerves communicated with the branches of the facial and buccal nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
66
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 14 publications
9
66
1
2
Order By: Relevance
“…The formation of the accessory mental foramen was attributed by some authors to the occurrence of earlier separation of the mental nerve (Naitoh et al, 2009). Additionally, variations in the incidence of accessory mental foramen between ethnic groups are present (Toh et al, 1992;Sawyer et al). In the present study, we observed accessory mental foramina in 7.3 % of the cases.…”
Section: Discussionsupporting
confidence: 64%
“…The formation of the accessory mental foramen was attributed by some authors to the occurrence of earlier separation of the mental nerve (Naitoh et al, 2009). Additionally, variations in the incidence of accessory mental foramen between ethnic groups are present (Toh et al, 1992;Sawyer et al). In the present study, we observed accessory mental foramina in 7.3 % of the cases.…”
Section: Discussionsupporting
confidence: 64%
“…Three accessory MFs were found in three Japanese cadavers and their diameters were 0.74 mm, 0.80 mm and 0.89 mm and were relatively smaller than normal MF [7]. Distances between MF and accessory MF were 0.67 mm, 2.1 mm and 5.74 mm [7].…”
Section: Introductionmentioning
confidence: 83%
“…In the study of sixty-nine adult Thai mandibles, the mean distance from the MF to the Symphysis Menti, lower border of the mandible and posterior border of the mandibular ramus was 28.83 mm, 68.85 mm and 14.88 mm respectively [6]. Three accessory MFs were found in three Japanese cadavers and their diameters were 0.74 mm, 0.80 mm and 0.89 mm and were relatively smaller than normal MF [7]. Distances between MF and accessory MF were 0.67 mm, 2.1 mm and 5.74 mm [7].…”
Section: Introductionmentioning
confidence: 99%
“…Buccal foramina showing continuity without the MC are considered to be the so-called nutrient foramina (5). AMFs normally occur singly, but the number can range from 1 to 3 foramina per side (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%